Determining service improvement priority in a zoological park - Ronald Sukwadi; Ching-Chow Yang (Journal of Industrial Engineering and Management (JIEM), 2014)
Purpose: The objective of this research is to determine the service improvement priority based on tourist judgements and experiences on service quality in a zoological park. Design/methodology/approach: A powerful integrated model was developed to acquire accurate critical service attributes and their priority ranks that can promote tourist satisfaction and tourist loyalty. Drawing on relevant literature, a model was proposed based on tourists' perspective by integrating structural equation model (SEM) with SERVQUAL and refined Kano models. Findings and Originality/value: Based on the analysis of data through some quantitative tools, the study helped in prioritizing the critical service attributes, which, if adopted, improved, and implemented, could lead to satisfaction of tourists. This will help a zoological park to propose more efficient and value-added improvement policies of the service. Research limitations/implications: The primary limitation in the scope its sample. Because the study involved only one Zoological Park in Indonesia, the results cannot be generalized across a national wide spectrum. Originality/value: The study was the first to successfully apply an integrated model in tourism sector, which has previously not been used. The study has hopefully opened up an area of research and methodology that could provide considerable further benefits for researchers interested in this topic. Moreover, the integrated model has proven to be useful in determining the priority rank of critical service quality attributes.
Keywords: 650; SERVQUAL; refined Kano model; SEM; service attributes; improvement priority